Modifying behavior of calcined waste phosphorus slag on the dispersivity and mechanical properties of dispersive soil - Gaowen Zhao; Tao Wu; Guanzhou Ren; Dongyang Yan; Zhen Zhu; Shijun Ding; Mei Shi; Henghui Fan (Soils and Foundations)
Dispersive soil is a common problem soil in engineering projects, which has the potential risk of causing serious engineering failures. In this paper, calcined waste phosphorus slag (CPS) was chosen to enhance the mechanical properties and reduce soil dispersivity. Dispersive soil samples with 1 % to 10 % CPS content were prepared and cured for 0 to 28 days. The dispersivity identification test was used to assess soil sample dispersivity. The compressive and tensile strength, conductivity, and pH were determined for the soil. Microstructural and mineral composition were analyzed using SEM/EDS, TG/DTG, and XRD analysis. The natural dispersive soil was selected to verify the effect of CPS in improving soil. Experiments show that the CPS inhibits soil dispersivity and converts it into non-dispersive soil. Both compressive and tensile strength increases significantly with the increase in the content of CPS and curing time. The tensile strength of the soil samples cured for 28 days increased by about 76 % and the compressive strength by about 61 % as the mixed content of CPS was increased from 1 % to 10 %. Results show that CPS can improve the strength and modify the dispersivity of soil, its optimal mixing content is 5 %. In addition, using CPS in dispersive soil could also solve the disposal problem of phosphate slag, which is a win-to-win solution.